The Role of Sphingolipids in Allergic Disorders - Díaz-Perales, Araceli; Escribese, Maria M.; Garrido-Arandia, María; Obeso, David; Izquierdo-Alvarez, Elena; Tome-Amat, Jaime; Barber, Domingo (Frontiers in Allergy, 2021)
Allergy is defined as a complex chronic inflammatory condition in which are implicated genetic and environmental factors. Sphingolipids are involved in multiple biological functions from being key cell membrane components to critical signalling molecules. To date, sphingolipids have been studied in different human pathologies such as neurological disorders, cancer, autoimmunity and infections. Sphingolipid metabolites, in particular ceramide and sphingosine-1-phosphate, regulate a diverse range of cellular processes that are important in immunity and inflammation. Moreover, variations in the sphingolipid concentrations have been strongly associated with asthma. In addition, some bacteria strains dependent on sphingolipids are altered in the microbiota of allergic patients. This review will focus on the role of sphingolipids in the development of allergic sensitization and allergic inflammation through the activation of immune cells resident in tissues, as well as their role in barrier remodelling and anaphylaxis. The knowledge gained in this emerging field will help to develop new therapeutic options for inflammatory disorders.